Dobbs and the future of health data privacy for patients and healthcare organizations. (4th October 2022) - Clayton, Ellen Wright; Embí, Peter J; Malin, Bradley A
Abstract: The Supreme Court recently overturned settled case law that affirmed a pregnant individual's Constitutional right to an abortion. While many states will commit to protect this right, a large number of others have enacted laws that limit or outright ban abortion within their borders. Additional efforts are underway to prevent pregnant individuals from seeking care outside their home state. These changes have significant implications for delivery of healthcare as well as for patient-provider confidentiality. In particular, these laws will influence how information is documented in and accessed via electronic health records and how personal health applications are utilized in the consumer domain. We discuss how these changes may lead to confusion and conflict regarding use of health information, both within and across state lines, why current health information security practices may need to be reconsidered, and what policy options may be possible to protect individuals' health information.